The Eagle Eyes: an Intervention Utilizing Visual Thinking Strategies to Enhance the Observation Skills of Medical Students - Najmeh Ghorbani; Maryam Alizadeh; Azadeh Sayarifard; Abdoljavad Khajavi; Philip Yenawine (BMC Medical Education)
Abstract Background Visual Thinking Strategies (VTS) is an evidence-based pedagogical approach that uses art analysis and structured inquiry to enhance observation, critical thinking, and teamwork, especially in medical training for clinical skills development. This study aimed to compare the short-term and delayed follow-up effects of integrating Visual Thinking Strategies and Visual Thinking Activity (VTA) tasks based on the PRISM Model with Observation Exercises (OE) on medical students’ observation skills, including the number of observations, number of words used, and time spent describing observations. Method This pre- and post-test experimental study with a control group was conducted among first-year medical students at Gonabad University of Medical Sciences during the 2023–2024 academic year. Forty-four students participated in the intervention group, receiving VTS and VTA tasks, while 45 students formed the control group, engaging in OE alone. Observation skills were assessed using standardized art images (short-term) and real-world clinical exposure (delayed follow-up) through measures of total observations, number of words used, and time spent describing observations. Descriptive statistics, analysis of one-way ANOVA/ANCOVA, and independent t-tests were employed for data analysis. Results In the short-term evaluation, the intervention group demonstrated significantly higher performance in the total number of observations (p = 0.001, Adjusted Partial Eta2 = 0.12), number of words used to describe art images (p = 0.001, Adjusted Partial Eta2 = 0.21), and time spent analyzing images (p < 0.001, Adjusted Partial Eta2 = 0.17) compared to the control group. However, after one month in a clinical exposure, no significant differences were found between the groups in the total number of observations (p = 0.62) and number of words used (p = 0.64). Nevertheless, the intervention group spent significantly more time describing their clinical observations (p = 0.04, Effect Size = 0.44). Conclusion The findings highlight the significant role of VTS in enhancing medical students’ observation skills. While both interventions were equally effective in the delayed follow-up and real-world settings regarding the total number of observations and words used, the VTS and VTA approach led to a notable increase in the time spent on observation descriptions. This conclusion warrants further investigation in future studies.